1999
DOI: 10.1038/sj.bjc.6690314
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and mismatch repair gene inactivation in sporadic pancreatic and colon tumours

Abstract: Summary Genomic instability has been proposed as a new mechanism of carcinogenesis involved in hereditary non-polyposis colorectal cancer (HNPCC) and in a large number of sporadic cancers like pancreatic and colon tumours. Mutations in human mismatch repair genes have been found in HNPCC patients, but their involvement in sporadic cancer has not been clarified yet. In this study we screened 21 pancreatic and 23 colorectal sporadic cancers for microsatellite instability by ten and six different microsatellite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 31 publications
2
25
0
3
Order By: Relevance
“…We detected an aberrant hMLH1 promoter methylation in 75% of MSI-H gastric carcinoma cases leading to the absence or diminished expression of hMLH1. This percentage fits with those previously reported for SGC (Fleisher et al, 1999;Kang et al, 1999;Leung et al, 1999;Toyota et al, 1999;Wu et al, 2000;Yamamoto et al, 1999), sporadic colorectal carcinomas (Cunningham et al, 1998;Ghimenti et al, 1999;Kang et al, 1999), and endometrial carcinomas displaying MSI (Esteller et al, 1998;Simpkins et al, 1999). The RT-PCR analysis of hMLH1 expression showed that there is a significant association between hMLH1 hypermethylation and loss of hMLH1 expression as previously reported by Deng et al (1999).…”
Section: Discussionsupporting
confidence: 79%
“…We detected an aberrant hMLH1 promoter methylation in 75% of MSI-H gastric carcinoma cases leading to the absence or diminished expression of hMLH1. This percentage fits with those previously reported for SGC (Fleisher et al, 1999;Kang et al, 1999;Leung et al, 1999;Toyota et al, 1999;Wu et al, 2000;Yamamoto et al, 1999), sporadic colorectal carcinomas (Cunningham et al, 1998;Ghimenti et al, 1999;Kang et al, 1999), and endometrial carcinomas displaying MSI (Esteller et al, 1998;Simpkins et al, 1999). The RT-PCR analysis of hMLH1 expression showed that there is a significant association between hMLH1 hypermethylation and loss of hMLH1 expression as previously reported by Deng et al (1999).…”
Section: Discussionsupporting
confidence: 79%
“…The presence of novel fragments in amplified products of cancer DNAs compared with those of reference DNAs is a strong indicator of genomic instability. Frequent MSI has been reported in colorectal carcinoma and some other solid tumors (Ghimenti et al, 1999). There were controversies in previous reports with regard to the incidence of MSI in HCC (Salvucci et al, 1999;Sheu et al, 1999).…”
Section: Microsatellite Instability Is Rare In Hcc Specimens From Soumentioning
confidence: 98%
“…There may also be an increase in risk for those with familial adenomatous polyposis [19] and Lynch syndrome II [29] . Conflicting data are available about the increased relative risk related to diet [30,31] (high intake of fat and meat), coffee and alcohol consumption [32,33] , aspirin and NSAID use [34][35][36] , past partial gastrectomy [37] or cholecystectomy [38] .…”
Section: Risk Factorsmentioning
confidence: 99%
“…These genes are related to hereditary non-polyposis colorectal cancer (HNPCC), and loss of their function can justify the increased risk of pancreatic cancer in families with a history of HNPCC [19] .…”
Section: Dna Mismatch Repair Genesmentioning
confidence: 99%